Instructional Pedagogical Strategies for Reading Comprehension in Elementary Schools: A Problem-Based Analysis - Apfani, Sry; Suryani, Ade Irma; Ramadhan, Syahrul; Sukma, Elfia; Binti Jamalluddin, Norliza; Bin Sihes, Johari (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Reading comprehension is a fundamental skill in primary education as it plays a critical role in supporting students’ understanding of various subject areas. However, many elementary school students still experience difficulties in comprehending texts effectively. This study aims to identify problems in reading comprehension learning and to formulate instructional pedagogical strategies to improve students’ reading comprehension. A descriptive qualitative approach was employed using a survey method. Data were collected through open- and closed-ended questionnaires distributed to 81 classroom teachers of grades 3 to 6 across elementary schools in West Sumatra. The findings indicate that although students demonstrate relatively high interest in reading, they encounter difficulties in identifying main ideas, retaining information, and connecting texts with prior knowledge. These problems are influenced by monotonous teaching methods, limited instructional media, unsupportive classroom environments, and diverse socio-economic backgrounds. The results also reveal the need for more interactive, contextual, and collaborative reading instruction supported by varied pedagogical strategies. Therefore, this study proposes instructional pedagogical strategies emphasizing interactive reading activities, collaborative discussions, contextual text engagement, and differentiated reading support to enhance students’ reading comprehension. These strategies provide practical guidance for teachers in designing more effective reading instruction and fostering active student participation. The implementation of structured pedagogical strategies is expected to improve students’ reading comprehension skills and support their overall academic development in elementary education.